Relationship of Local Soybean Processing To Scarcity of Soybean During Pandemic - Muhamad Ahjan; Ikomatussuniah Ikomatussuniah (Leuit (Journal of Local Food Security), 2022)
The scarcity and rising price of soybeans is a problem that the Indonesian government is very concerned about. The main reason for the increase in soybean prices is because soybean supplies from the United States are running low due to the COVID-19 pandemic. This problem is inseparable from the large portion of soybean imports in Indonesia. So far, domestic soybean production is still lacking and most of it is imported from foreign countries. The formulation of the problem is How is the Relationship between Local Soybean Processing During the Pandemic and Government Policies or Solutions Regarding Local Soybean Crops?. The research method carried out by the author is research with a qualitative descriptive approach. Qualitative research is research steps that are carried out descriptively in the form of written and unwritten words from the perpetrators, qualitative research focuses on aspects of quality, the value behind a fact. The Central Statistics Agency (BPS) noted that the price of soybean imports to Indonesia reached US$1.48 billion in 2021. This value reached 47.77% from US$1 billion in 2020. The United States is still the largest soybean importer with a value of US$ 1.28 billion in 2021. This value is equivalent to 86.78% of the total soybean imports that enter Indonesia. Many efforts have been made by the government to reduce the dependence of the Indonesian people on imported soybeans and become a solution and overcome the increase in soybean prices that have suppressed tofu and tempeh craftsmen some time ago.